Occurrence of co-existing blaVIM-2 and blaNDM-1 in clinical isolates of Pseudomonas aeruginosa from India. Issue 1 (December 2016) - Paul, Deepjyoti; Dhar, Debadatta; Maurya, Anand; Mishra, Shweta; Sharma, Gauri; Chakravarty, Atanu; Bhattacharjee, Amitabha
Abstract Background bla VIM-2 harboringPseudomonas aeruginosa has been reported worldwide and considered as the most prevalent metallo-β-lactamase after NDM which are found horizontally transferable and mostly associated with integron gene cassettes. The present study investigates the genetic background, transmission dynamics as well as stability ofbla VIM-2 in clinical isolates ofP. aeruginosa harborbla NDM-1 as well which were collected from October 2012 to September 2013. Methods TwoP. aeruginosa strains harboringbla VIM-2 along withbla NDM-1 were isolated from Silchar Medical College and Hospital, India. Genetic environment of these resistance determinants was determined and transferability was checked by transformation and conjugation assay which was further confirmed by Southern hybridization. Replicon typing was performed to determine the incompatibility group of the resistant plasmid and their stability was checked by serial passage method. Antimicrobial susceptibility pattern of the isolates was determined and their clonal relatedness was checked by pulsed field gel electrophoresis. Results bla VIM-2 was found to be horizontally transferable through an Inc F type plasmid of approximately 30 kb in size.bla VIM-2 was found to be associated with integron gene cassette and was flanked by two different types of cassette arrays. Both the isolates were co-harboringbla NDM-1 which was carried within Inc N type of plasmid with an approximate 24 kb in size and associated with ISAba125 in their upstream region. Reduced susceptibility rate as well as high MIC range was observed in case of wild strains and transformants carryingbla VIM-2 andbla NDM-1 . Conclusions The detection of this co-existence of multiple carbapenem resistance genes in this part of world is worrisome and further investigation is required in order to trace the source and to initiate proper treatment option.